Peningkatan Soft Skills Pribadi Konselor Mahasiswa BKI Melalui kegaitan Career Development Program (CDP) - Triyono, Triyono; Al-Ghozaly, Syakirin; Imanti, Vera (Universitas Islam Negeri Raden Intan Lampung, 2018)
Soft skills are a set of abilities related to adjustments to oneself, others, and the environment. The counselor's personal soft skills mean the abilities or personal competencies possessed by a counselor. This study aims to determine how much the Career Development Program (CDP) influences in developing the counselor's personal soft skills of BKI students. The design of this research is quantitative experimental, using the pre-experimental design method with the type of pre-test and post-test one group design. The population of this study were the students of Islamic Guidance and Counseling (BKI) IAIN Surakarta 2015/2016, 2016/2017, and 2017/2018 academic years. The sample in this study were 90 students by taken in 3 classes in each academic year, through stratified cluster random sampling. Measurement of the counselor's personal soft skills using EPPS psychological instruments. The research results of the counselor’s personal soft skills of BKI students before and after being given Career Development Program (CDP) training, both in the second semester, 4th semester and 6th semester students groups showed significant differences. The results of paired t-test analysis obtained the pretest and posttest values with sig values = 0.000 <0.05. This means that the Career Development Program (CDP) has a significant effect on improving the counselor's personal soft skills of BKI students. The Career Development Program (CDP) is a model for the development and improvement of personal counselor’s soft skills that are effective for the students of BKI IAIN Surakarta